Problems of employment in the Republic of Kazakhstan - Zhanabayeva , Aktureeva, Zh., E. K., A. (Journal of Economic Research & Business Administration, 2016)
The labor market is one of the most important, the level of which is an indicator of the state of the economy as a whole and its main condition for the proper functioning of economic growth. The article defines the relevance of the research topic, assesses the current state of the labor market in the Republic of Kazakhstan. The analysis of unemployment rates and employment over the past few years. Specificity of Kazakhstan and most of its regional labor markets is the high level of self-employment. The analysis identified the problems associated with self-employment in the various regions of Kazakhstan, by sectors and industries. The main problems hindering the development of the labor market in Kazakhstan is the problem of population employment, self-employment in rural areas, youth unemployment. Recommendations for improvement of the main indicators of the labor market, which will help ensure efficiency of employment, reducing unemployment, improving the quality and competitiveness of the labor force in Kazakhstan.